Mosby's physical examination DVD series : DVD 1 : neurologic system : mental status and cranial nerves [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 17 minute video shows the steps needed to perform two major parts of the neurologic examination: assessment of mental status and cranial nerves. With the patient seated, it demonstrates how to evaluate the patient's general appearance and behavior, cognitive abilities, emotional stability, and speech and language skills as well as the functioning of all twelve pairs of cranial nerves, using the appropriate equipment. The video shows expected findings in healthy adults and presents variations in assessment techniques and expected findings in pediatric and geriatric patients."--Publisher's website.